2019
DOI: 10.36998/jkmm.v7i2.64
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Aktivitas Fisik Dan Body Image Dengan Status Gizi Siswi Sma Yayasan Pupuk Kaltim Bontang

Abstract: Nutritional status is a condition caused by a balanced between nutrient intake and nutritional requirements for metabolism. In Indonesia, the prevalence of overweight 15.1% and underweight 4.7%. This study aims to determine the relationship between physical activity and body image with nutritional status of students in senior high school of Yayasan Pupuk Kaltim Bontang. This study was an observational analytic with cross sectional study. The sampling procedure was purposive sampling according to the inclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…The correlation of the application of balanced nutrition guidelines and body image with nutritional status at SMK Nusantara 2 Kesehatan 2016 (Permatasari and Setiawati, 2017) Design: Observational, cross-sectional Subjects: 121 female students aged 15-18 years Data collecting: interviews with the food recall questionnaire, PAL, and the Body Shape Questionnaire (BSQ-34) Data analysis: Chi-Square Most of the respondents (70.2%) had normal nutritional status, adequate carbohydrate intake (90.1%), adequate fat intake (54.5%), adequate protein intake (67.8%), light physical activity (79%), the habit of do not have breakfast every day (52.9%) and negative body image (66.9%). Bivariate test result showed that there were correlation between body image (p<0.05; OR=3.333), protein intake (p<0.05; OR: 3.632), fat intake (p<0.05; OR=12.000) and physical activity (p<0,05; OR 6.146) with nutritonal status in female students Correlation of physical activity and body image with nutritional status of high school students SMA Yayasan Pupuk Kaltim Bontang (Prisilia, Rachmi, and Aminyoto, 2019) Design: Observational, cross-sectional Subjects: 262 students of class X, XI, and XII with purposive sampling technique Data collecting: physical activity and body image perception with the help of a questionnaire, measurement of BMI (weight and height) Data analysis: the Kolmogrov-Smirnov test There was a significant correlation of body image and nutritional status of students (p = 0.000) (p <0.05) but there was no correlation of physical activity and nutritional status (p = 0.000) (p> 0.05).…”
Section: Results Research Methods Research Title and Authormentioning
confidence: 97%
See 1 more Smart Citation
“…The correlation of the application of balanced nutrition guidelines and body image with nutritional status at SMK Nusantara 2 Kesehatan 2016 (Permatasari and Setiawati, 2017) Design: Observational, cross-sectional Subjects: 121 female students aged 15-18 years Data collecting: interviews with the food recall questionnaire, PAL, and the Body Shape Questionnaire (BSQ-34) Data analysis: Chi-Square Most of the respondents (70.2%) had normal nutritional status, adequate carbohydrate intake (90.1%), adequate fat intake (54.5%), adequate protein intake (67.8%), light physical activity (79%), the habit of do not have breakfast every day (52.9%) and negative body image (66.9%). Bivariate test result showed that there were correlation between body image (p<0.05; OR=3.333), protein intake (p<0.05; OR: 3.632), fat intake (p<0.05; OR=12.000) and physical activity (p<0,05; OR 6.146) with nutritonal status in female students Correlation of physical activity and body image with nutritional status of high school students SMA Yayasan Pupuk Kaltim Bontang (Prisilia, Rachmi, and Aminyoto, 2019) Design: Observational, cross-sectional Subjects: 262 students of class X, XI, and XII with purposive sampling technique Data collecting: physical activity and body image perception with the help of a questionnaire, measurement of BMI (weight and height) Data analysis: the Kolmogrov-Smirnov test There was a significant correlation of body image and nutritional status of students (p = 0.000) (p <0.05) but there was no correlation of physical activity and nutritional status (p = 0.000) (p> 0.05).…”
Section: Results Research Methods Research Title and Authormentioning
confidence: 97%
“…Physical activity for teenagers is not only beneficial for maintaining physical health or other body organs, but also mental health. Study by Prisilia, Rachmi and Aminyoto, (2019), explained that by doing physical activity, self-esteem in adolescents will increase. This self-esteem is important for psychological well-being, building a positive body image, increasing self-efficacy, and preventing the teenager from experiencing depression, anxiety, and high-risk behaviors such as consume/ abuse the drugs (example: weight loss drugs which are harmful to adolescent's health).…”
Section: Results Research Methods Research Title and Authormentioning
confidence: 99%
“…Prisilia [27] status gizi seseorang ditentukan oleh kebutuhan dan asupan zat gizinya, asupan dan kebutuhan yang seimbang akan menghasilkan status gizi yang baik. Ada beberapa faktor yang mempengaruhi status gizi remaja, dan aktivitas fisik salah satunya.…”
Section: Menurut Analisis Statistik Dengan Ujiunclassified